Mitochondrial DNA Fragmentation to Monitor Processing Parameters in High Acid, Plant‐Derived Foods. Issue 12 (10th November 2015) - Caldwell, Jane M.; Pérez‐Díaz, Ilenys M.; Harris, Keith; Hassan, Hosni M.; Simunovic, Josip; Sandeep, K.P.
Abstract: Mitochondrial DNA (mtDNA) fragmentation was assessed in acidified foods. Using quantitative polymerase chain reaction, C t values measured from fresh, fermented, pasteurized, and stored cucumber mtDNA were determined to be significantly different ( P > 0.05) based on processing and shelf‐life. This indicated that the combination of lower temperature thermal processes (hot‐fill at 75 °C for 15 min) and acidified conditions (pH = 3.8) was sufficient to cause mtDNA fragmentation. In studies modeling high acid juices, pasteurization (96 °C, 0 to 24 min) of tomato serum produced C t values which had high correlation to time‐temperature treatment. Primers producing longer amplicons (approximately 1 kb) targeting the same mitochondrial gene gave greater sensitivity in correlating time‐temperature treatments to C t values. Lab‐scale pasteurization studies using C t values derived from the longer amplicon differentiated between heat treatments of tomato serum (95 °C for <2 min). MtDNA fragmentation was shown to be a potential new tool to characterize low temperature (<100 °C) high acid processes (pH < 4.6), nonthermal processes such as vegetable fermentation and holding times of acidified, plant‐derived products.